Implementasi Layanan Home Visit dalam Mengatasi Kesulitan Belajar di Masa Pandemi (Studi Kasus di SDN Sukasari 03 Kecamatan Rumpin Kabupaten Bogor) - Rahayu, Intan; Chudari, Ima Ni'mah (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The study aimed to find out of implementation of home visit services in overcoming the learning difficulties of students of SDN Sukasari 03 Sukasari Village, Rumpin Subdistrict, Bogor Regency, as well as to know the supporting and inhibitory factors. A qualitative approach is used in this study and the method used is case study. Participants in this study were the Head of SDN Sukasari 03, the teacher, 3 students, and 3 parents. Obsevations, interviews, and documentation are the data collection tools in this study. The results showed that the implementation of visiting teachers at SDN Sukasari 03 was initiative of grade VI teachers, the planning carried out was that teachers and school first identify learning difficulties that need to get home visit services, then determine the names of students who need home visit services, and make an implementation schedule. In the process, the teacher communicates in advance to the principal. The teacher conveys purpose of his arrival, discusses the difficulties experienced by students, establishes cooperation with parents. Evaluation is done that during the home visit process such as planning by giving a letter of advance notice to students and parents so that when the teacher visits the parents do not feel confused, it is used as improvement material for the future. Follow-up is done for students whose learning has not been resolved so it is necessary to hold a home visit replay. Teachers always report to the principal accompanied by photo evidence of the implementation of the home visit. The supportive responses of parents, principals, and other teachers. The factors home visit services are the less supportive responses of parents, students who are less open to the difficulties they experience, transportation costs, distance between school and student homes, and unfaithful weather.